EFFECTS OF INTRAARTICULAR HYALURONIC ACID AND METHYL PREDNISOLONE ACETATE ON CARTILAGE IN A MODEL OF EXPERIMENTAL ARTHRITIS IN RATS - Şirzat Çoğalgil,; Orhan Karsan,; Lale Cerrahoğlu,; Mahir Uğur,; Halis Süleyman,; Cemal Gündoğdu,; Fazlı Erdoğan, (Archives of Rheumatology, 2002)
This experimental study was performed to determine the effects of intraarticular hyaluronic acid (HA) and methyl prednisolone acetate (MPA) in degenerative osteoarthritis. 0.2 ml 1% formaline were injected to the posterior right knee joints of 40 male rats. One week after the injections, 10 rats were killed and arthritis was determined histopathologically. The remained 30 rats were divided to three groups. First group received intraarticularly 0.05 ml HA (HA group), second group 0.05 ml MPA (MPA group) and third group 0.05 ml saline as controls. The injections were performed at 7., 14. and 21. days after the arthritis. 15 days after the end of these treatments, rats were killed and sections were examined histopathologically. There was no significantly difference in cartilage healing between MPA and control groups (p>0.05). However cartilage healing was significantly high in HA group compared to MPA and control groups (p<0.05). It was concluded that HA is more useful than MPA in the treatment of arthritis intraarticularly because of its positive effects on cartilage tissue.